Rewiring cellular networks by members of the Flaviviridae family - Neufeldt, Christopher; Cortese, Mirko; Acosta, Eliana G.; Bartenschlager, Ralf (Nature reviews. Microbiology, 2018)
In this Review, Bartenschlager and colleagues discuss howFlaviviridaeviruses rewire cellular pathways and co-opt organelles. They compare strategies employed by flaviviruses with those employed by hepaciviruses and discuss the importance of these virus-host interactions in the context of viral replication and antiviral therapies.